2021
DOI: 10.1016/j.xfre.2021.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous ovarian hyperstimulation syndrome in a pregnant woman with hypothyroidism: a case report

Abstract: Objective To study a rare case of spontaneous ovarian hyperstimulation syndrome in a naturally conceived pregnancy associated with overt hypothyroidism. Design Case report. Setting Endocrinology private practice. Patient(s) A 32-year-old woman who was 13 weeks pregnant with bilaterally enlarged ovaries presumed to be secondary to hypothyroidism. Intervention(s) Administration of levothyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…There are multiple aetiologies for the formation of ovarian cysts in Hashimoto’s disease and long-standing hypothyroidism, but the most convincing one is the cross-reactivity of TSH, FSH and luteinising hormone (LH) due to the sharing of a common alpha chain 2. It is also postulated that there are TSH receptors on ovarian follicles, which on binding with TSH sensitises the action of FSH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are multiple aetiologies for the formation of ovarian cysts in Hashimoto’s disease and long-standing hypothyroidism, but the most convincing one is the cross-reactivity of TSH, FSH and luteinising hormone (LH) due to the sharing of a common alpha chain 2. It is also postulated that there are TSH receptors on ovarian follicles, which on binding with TSH sensitises the action of FSH.…”
Section: Discussionmentioning
confidence: 99%
“…All these mechanisms can lead to multiple large cysts inside the ovary mimicking OHSS in the picture. Spontaneous OHSS in long-standing hypothyroidism has been described in the literature 2 4–7. Menstrual irregularities with hypothyroidism are well known but the occurrence is not documented in the literature, therefore the association of hypothyroidism with ovarian cysts is not established.…”
Section: Discussionmentioning
confidence: 99%
“…Through the analysis of 13 case reports on HT combined with OHSS in naturally pregnant women [42][43][44][45][46][47][48][49][50][51][52][53][54], it has been found that the average age of these patients was 26 years (M ± SD: 26 ± 4.26). Most pregnant women experienced OHSS between the 9th and the 14th weeks of pregnancy.…”
Section: Sohss Combined With Ht In Naturally Pregnant Womenmentioning
confidence: 99%
“…Furthermore, impaired thyroid function mediates attenuated gonadotropin secretion directly and through a rise in prolactin secondary to elevated TSH levels, which may also cross-react with FSH receptors, while elevated prolactin sensitizes the ovaries to gonadotropin action. Together, these effects enhance the risk of ovarian hyperstimulation syndrome in hypothyroid women [ 185 , 186 ]. Regardless, further investigation will be required to conclusively determine the pathways through which thyroid dysfunction is linked to a polycystic ovarian morphology since, as discussed previously, the mechanisms through which thyroid hormones may interact with the HPG axis or ovarian tissue are complex and multimodal.…”
Section: Thyroid Hormones and Reproductive Physiologymentioning
confidence: 99%